Antipathogenic Potential of a Polyherbal Wound-Care Formulation (Herboheal) against Certain Wound-Infective Gram-Negative Bacteria - Pooja Patel; Chinmayi Joshi; Vijay Kothari (Hindawi Limited, 2019)
This study investigated antipathogenic efficacy of a polyherbal wound-healing formulation Herboheal against three multidrug-resistant strains of gram-negative bacterial pathogens associated with wound infections. Herboheal was evaluated for its quorum-modulatory potential against three different human-pathogenic bacteria, first in vitro through the broth dilution assay and then in vivo in the model host Caenorhabditis elegans. Herboheal at ≥0.1% v/v was able to inhibit (19-55%) in vitro production of quorum sensing-regulated pigments in all these bacteria and seemed to interfere with bacterial quorum sensing by acting as a signal-response inhibitor. This formulation could compromise haemolytic activity of all three bacteria by ∼18-69% and induced their catalase activity by ∼8-21%. Herboheal inhibited P. aeruginosa biofilm formation up to 40%, reduced surface hydrophobicity of P. aeruginosa cells by ∼9%, and also made them (25%) more susceptible to lysis by human serum. Antibiotic susceptibility of all three bacteria was modulated owing to pretreatment with Herboheal. Exposure of these test pathogens to Herboheal (≥0.025% v/v) effectively reduced their virulence towards the nematode Caenorhabditis elegans. Repeated subculturing of P. aeruginosa on the Herboheal-supplemented growth medium did not induce resistance to Herboheal in this mischievous pathogen, and this polyherbal extract was also found to exert a post-extract effect on P. aeruginosa, wherein virulence of the Herboheal-unexposed daughter cultures, of the Herboheal-exposed parent culture, was also found to be attenuated. Overall, this study indicates Herboheal formulation to be an effective antipathogenic preparation and validates its indicated traditional therapeutic use as a wound-care formulation.